Small bowel hemangioma in a 7-years-old boy, complicated by bleeding - V. P. Gavrilyuk; E. V. Donskaja; D. A. Severinov (Вестник хирургии имени И.И. Грекова)
Small intestine hemangioma is a benign vascular tumor formation, accounts for 0.05 to 0.3 % of all gastrointestinal tumors. This article presents a rare clinical observation - intraluminal hemangioma of distal parts of the ileum in a boy of 7 years old, complicated by massive bleeding. The presented clinical observation shows the difficulty of diagnosis, as well as the preliminary diagnosis performed by a pediatric surgeon: Meckel’s diverticulum, complicated by bleeding. As we know, more than 70 % of cases of gastrointestinal bleeding in children are really associated with the pathology of Meckel’s diverticulum. This requires the transfer of such patients to a surgical hospital, performing surgical intervention for revision of the abdominal cavity and excision of the pathological formation, as well as additional surgical techniques depending on intraoperative tactics.The described case demonstrates effective diagnostic tactics and features of intraoperative picture, surgical treatment of patient based on laparotomy and resection of intestinal area. The possibility of achieving encouraging results of surgical treatment of this difficult category of patients with reasonable choice of surgical tactics in childhood has been demonstrated. It is obvious that the key to successful treatment of such patients is timely diagnosis, which is not easy task due to the morphological and topographic characteristics of the pathological focus.